The influence of Malay food towards international student - Chan Tian Ci; Che Amierul Azmi Che Azmi; Anis Adilla Mohamad Azlan; Nur Alia Syahamah Supian (2021)
Food is recognized as an expressive of identity and as something that can evoke feelings that can create emotional. Yet, it is a common problem among the international student is that they prefer to choose their own nation foods instead of trying new ones. In this study is focuses on the acceptance of Malay food among the international student. A quantitative method is used in completing this research. A Simple random sampling is used to collect a data and analysed with Statistical Package for Social Science (SPSS) version 26. The result finding is support all the variables. The result indicate that many factors lead to attempting of international student to try Malay food. Although Malaysia is considered as food paradise, however there still a lot of work need to be done to make Malaysia’s food culture globally recognised and need to maintain its uniqueness to ensure that the food quality doesn’t drain out over generation. Hopefully, the information provided during this research can help the relevant parties to introduce the Malaysia’s food culture, which in turn make Malaysia to be globally recognised by the whole world.